Hybrid Cloud Workload Optimization with Generative AI: Technical Article Outline - Vijayakumar Jayaseelan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of generative AI technologies in optimizing hybrid cloud environments, presenting a multifaceted analysis of current capabilities and emerging trends. The article examines how artificial intelligence fundamentally reshapes resource management through predictive allocation mechanisms, pattern recognition, and real-time demand analysis, shifting hybrid cloud operations from reactive to proactive paradigms. It evaluates critical security considerations including multi-zone deployments, AI-driven threat analysis, unified identity management, and zero-trust architectures that maintain protection across heterogeneous infrastructures. Network optimization strategies are analyzed, featuring software-defined technologies, latency minimization techniques, end-to-end encryption methodologies, and proximity-based workload allocation approaches that enhance performance while maintaining security. Implementation insights from enterprise case studies demonstrate significant improvements in application performance, resource utilization, and cost efficiency, while highlighting organizational factors critical for successful adoption. The article concludes by examining future technological horizons including advanced generative AI capabilities, quantum computing integration, and autonomous optimization systems, providing a strategic roadmap for organizations navigating the evolving hybrid cloud landscape.
Keywords: Generative AI; Hybrid Cloud Optimization; Workload Management; Security Architecture; Autonomous Infrastructure